Perancangan Data Warehouse Untuk Prediksi Penjualan Pada Orba Express Menggunakan Pentaho - Pratama, I Putu Agus Eka; Widhiasih, Ni Putu Nirmala Dewi (JUSS (Jurnal Sains dan Sistem Informasi), 2020)
The Data Warehouse is a large data Storage facility or something called a Data Warehouse. The human work that requires so much data makes it harder to do it by hand. Such large amounts of data then hinder one from managing the data and predicting the products that are so popular by consumers that they decide to store them in the Data Warehouse. The Data Warehouse is the solution to the problem to predict a sale of a product. The Data Warehouse is a system that can extract, clean, adapt, and send a source of data into a data Storage or Data Warehouse which then implement through tools Pentaho in order to be able to analyze data. The purpose of the Data Warehouse design was to be able to mitigate shop owners' efforts on decision-making, like deciding what products sell to stock stores so they can reduce the stores' built-up. Keywords: Data Warehouse, Storage, Pentaho.